Revisión sistemática del Cuestionario Factorial de Personalidad (16PF) (2011)
ABSTRACT: This paper seeks to establish the use and impact of the 16PF personality test in academic journals during period 2000-2010. To achieve this goal we use a methodology of a systematic literature review of 30 articles meeting the inclusion criteria. We have observed that test has been used often in several studies around the world, although there is a discussion about using issue No. 4 because it has not good psychometric properties. The country in which most studies were found was Spain, followed by the USA. The first one is characterized by a research to identify personality traits in different populations while the second one has a large number of psychometric research instruments. Finally, we recommend to broad the time criteria for an article inclusion in order to identify fully the development of the instrument and its use.